The amazing diversity of the genus Monospilus Sars, 1862 (Crustacea: Branchiopoda: Aloninae) in South America - Sousa, Francisco Diogo R.; Elmoor-Loureiro, Lourdes M. A.; Panarelli, Eliana A. (Zootaxa, 2017)
The main goal of this paper is to describe three new species of the genus Monospilus Sars, 1862 (Crustacea: Cladocera). Monospilus macroerosus sp. nov. differs from other species of the genus in several peculiar morphological traits, the most striking being the presence of a saw-shaped pecten of teeth on the postabdominal claw. This species inhabits semiterrestrial habitats (wet leaf litter on hydromorphic soil from gallery forest), exhibiting adaptations related to movement and food handling in this type of habitat. Monospilus brachyspinus sp. nov. inhabits truly aquatic habitats, where lives being associated with macrophytes and submerged leaves. It may be recognized by the postabdominal claw, which is armed with proximal spinulae modified in a short spine. In Monospilus sp., the proximal spinulae are modified in a long and slender spine. So far, Monospilus sp. occurs in southern South America, while Monospilus macroerosus sp. nov. and Monospilus brachyspinus sp. nov. occur in the Cerrado biome in Brazil, in the central portion of South America. Some conclusions about the conservation status of new species also are made.